Immunophenotyping characteristics and clinical outcome of COVID-19 patients treated with azvudine during the Omicron surge - Qiu, Meihua; Song, Xiaogang; Zhang, Qianqian; Zou, Shenchun; Pang, Lingling; Nian, Xueyuan (Frontiers in Immunology, 2024)
BackgroundLittle is known about immunophenotyping characteristics and clinical outcomes of COVID-19 patients treated with azvudine during the Omicron variant surge.MethodsThis study enrolled patients diagnosed with COVID-19 from December 2022 to February 2023. The primary outcome was defined as all-cause mortality, along with a composite outcome reflecting disease progression. The enrolled patients were followed for a period of 60 days from their admission.ResultsA total of 268 COVID-19 patients treated with azvudine were enrolled in this retrospective study. The study found that the counts of lymphocyte subsets were significantly reduced in the composite outcome and all-cause mortality groups compared to the non-composite outcome and discharge groups (all p < 0.001). Correlation analysis revealed a negative association between lymphocyte subsets cell counts and inflammatory markers levels. The receiver operating characteristic (ROC) curve analysis identified low CD4+ T cell count as the most significant predictor of disease progression and all-cause mortality among the various lymphocyte subsets. Additionally, both the Kaplan-Meier curve and multivariate regression analysis demonstrated that low CD4+ T cell count level (< 156.00 cells/μl) was closely associated with all-cause mortality in COVID-19 patients treated with azvudine.ConclusionsA low CD4+ T cell count may serve as a significant predictive indicator for identifying COVID-19 patients receiving azvudine treatment who are at an elevated risk of experiencing adverse outcomes. These findings may offer valuable insights for physicians in optimizing the administration of azvudine.